Prevalence of economic violence among the geriatric population and their knowledge and utilization of social security schemes in Chengalpattu district, Tamil Nadu - Divyabharathy Ramadass; Sangeethapriya Sivaprakasam; Murugan Venkatesan (Journal of Family Medicine and Primary Care)
Context: Economic independence is an important factor in the prevention of violence among the elderly. Optimal utilization of various social security schemes in India helps them in achieving financial independence and proper utilization of health care services. However, there is a knowledge and service utilization gap among the elderly in our population. Aim and Objectives: To assess the prevalence of economic violence and awareness and utilization of social security schemes among the geriatric population. Settings and Design: Community-based cross-sectional study conducted in rural and urban field practice areas of the tertiary care center. Methods and Material: A simple random sampling method was adopted. The data were collected using a pilot-tested semistructured questionnaire among 406 participants from three selected villages and wards of Venmalagaram and Maduranthakam during January to July 2023. Statistical Analysis Used: Frequencies and proportions were used for categorical variables, and Chi-square test was applied to test the level of significance. P <0.05 was considered statistically significant. Results: The prevalence of economic violence was found to be 12.1%. Among them, neglect was seen in a major proportion (61.2%). Awareness about the old age pension was seen in 70.7%, followed by Annapurna scheme (17%) and PMVVY (4.9%). The utilization of these schemes was found to be 34.0%, 11.6%, and 2.7%, respectively. Conclusions: The prevalence of economic violence among the geriatric population was in the form of neglect and property misuse. The knowledge and utilization of social security schemes were poor among the elderly.